(untitled) (World Economics and Finance Bulletin, 2025)
The rapid expansion of e-commerce has significantly transformed the global retail landscape, presenting new challenges for taxation authorities. Turnover tax in online sales has become a critical subject in tax policy, necessitating effective strategies for fair revenue collection while ensuring business compliance. This article examines the implications of turnover tax in e-commerce, exploring its economic effects, legal frameworks, and enforcement mechanisms. By analyzing case studies and international practices, we aim to provide insights into optimizing taxation policies to accommodate the digital economy.